Ammonium nitrate with improved properties for agricultural crops - Kodirov Bekzod; Mamatov Khamidulla; Yusupov Abdulkhamid; Kuziboev Shoirjon; Rustamov Mukhammadazim (BIO Web of Conferences)
This article presents the results of research aimed at developing enhanced mineral fertilizers based on ammonium nitrate. The main objective was to improve the quality and strength of fertilizer granules by adding local unconventional natural minerals and technogenic wastes to ammonium nitrate. During the research, bentonite and glauconite powders, along with lime-quenching residues, were introduced into the ammonium nitrate solution to identify optimal formulations and proportions. The experiments demonstrated that granules produced with the new additives significantly surpassed conventional ammonium nitrate granules in strength and were enriched with microelements. Field trials confirmed that the application of these newly developed fertilizers considerably increased the productivity of agricultural crops. The technology developed through this research effectively expands the variety of mineral fertilizers available and has practical significance in enhancing agricultural efficiency.